Eliciting empathetic drives to prosocial behavior during stressful events - Grignoli, Nicola; Filipponi, Chiara; Petrocchi, Serena (Frontiers in Psychology, 2022)
In the current pandemic situation, psychological science is increasingly considered by public health policy. Empathy is mainly recognized as a crucial drive for prosocial behaviour. However, this rich body of evidence still lacks visibility and implementation. Effective social programmes are needed, and little is known about how to elicit empathetic drives. The paper gives first a clear foundation to the role of empathy during stressful events. It provides then a comprehensive overview of innovative interventions triggering empathic response in the public such as fiction, film, and theatre. Moreover, it integrates interactive ways of sharing personal views that could elicit empathetic feelings in different people. Advances deriving from this perspective could be of significant public interest in the current and future health crises and help authorities develop innovative social programmes, which should be the focus of further scientific inquiry.